Subjectivity and identity in detention: Punishment and society in a global age - Bosworth, M (SAGE Publications, 2012)
This article draws on ethnographic research that I conducted in five British immigration removal centres from November 2009 to June 2011, and considers the challenges these institutions pose to our understanding of penal power. These centres contain a complex mix of foreign national citizens including former and current asylum seekers, those without visas, visa over-stayers and post-sentence foreign national prisoners. For many non-British offenders, a period of confinement in an immigration detention centre is now, effectively, part of their punishment. What are the implications of this dual confinement and (how) can we understand it within the intellectual framework of punishment and society? © The Author(s) 2012.